Formação de professores no enfoque CTSA: uma experiência com licenciandos em ciências biológicas em Sergipe - Santana, Sebastiana Érica Cruz (2020)
The teaching profession is one of the careers built not only during the undergraduate course,but also during the personal trajectory. The role of this professional in society is of great importance for students to understand the scientific and technological changes that occur constantly. Governmental initiatives aimed at improving teacher training in Brazil are still few compared to other countries. The use of the STS(E) approach (Science-TechnologySociety-Environment) in the teaching of Science and Biology can contribute to the formation of critical citizens and able to make more conscious decisions, considering the context in which they are inserted. However, different factors influence its implementation, one of which is teacher training that is not contextualized with the needs of society. Thus, it is important to provide opportunities, from the undergraduate courses, discussions about the STS approach (E) so that future teachers realize its relevance and feel safe to work on disciplinary topics in this perspective. Therefore, the objective of this work is to analyze the effects and implications of the insertion of the STS(E) approach in the improvement of the teaching formation of undergraduate students in Biological Sciences. To this end, a qualitative research of the action-research type was carried out, developed during the classes of the discipline “Instrumentation for the Teaching of Sciences and Biology” (45 classhours), mandatory in the Biological Sciences course at the Federal University of Sergipe. It was possible to identify that, until the beginning of the classes of this discipline, in the 5th curricular period, the undergraduates still did not know the STS(E) perspective. In this way, four classes were given to present and discuss this topic, in order to encourage students to develop didactic workshops in this perspective, in the discipline, to be developed with students from the Application College of UFS. In sequence, the undergraduate students, organized into eight groups, were instructed to develop one activity per group, addressing different topics under the STS(E) approach, with elementary and high school classes. After analyzing the activity developed, different levels of STS(E) were evidenced, using the classification of Pedretti and Nazir, there are six categories: Design, Historical, Logical reasoning, Centered value, Sociocultural and Socio-Eco-fair, of these, only three were present in the activities produced. At the end of the course, the undergraduates rated their experience as positive, for many the first in front of a class, with most of them (80%) considering the STS(E) approach of extreme importance for Science and Biology Education. However, 50% of the class stated that its implementation is only possible "partially", having been given different justifications for this statement, such as the overcrowding of classrooms, the lack of knowledge of teachers and traditional teaching as a barrier to be exceeded. It is concluded that inserting more critical approaches in the initial training of science and biology teachers is as necessary as in basic education. Although there are difficulties in its implementation, it is urgent to initiate actions in this direction, if we aim for a society more aware of the nature of science and its influence on the construction and social dynamics.